Memórias resistentes: as construções das memórias das ditaduras no Brasil e na Argentina a partir da preservação de edifícios da repressão - Silva, Elson Luiz Mattos Tavares Da [UNIFESP] (2018)
Between The Years Of 1960 And 1970 Latin America Experienced Successive Military Coups For The Installation Of National Security Dictatorships. The 1980s, On The Other Hand, Were Marked By The Political Reopening In Some Of These Countries. Understanding That These Political Processes, Traumatic Due To The Great Violence In Several Senses, Generated Harsh Memories, Has Created A Challenge To The Perspective Societies: What To Preserve Or What To Forget? Considering All Particularities Of Each Process, These Dictatorships Were Characterized By Institutionalization Violence And The Centrality Of Repression In Their Regimes. Some Institutions Of Repression Worked Systematically, Producing The Reality Of Terror, Based In Arrestements, Kidnappings, Torture, Disappearances, Murders And Other Violence. In This Sense, The Preservation Of Places Where Terror Organs Have Functioned Has Been An Important Instrument For, At Least, The Public Recognition Of This Violent Past. The Procedures For Creating These Places Of Mem